0849 Sleep Disturbance in Women with and Without HIV: The Role of Psychosocial Factors. (12th April 2019) - Burgess, Helen J; Weber, Kathleen M; Burke-Miller, Jane; McClellan, Leah; Daubert, Elizabeth; Bond, Caitlin; Morack, Ralph; Cohen, Mardge; French, Audrey
Abstract: Introduction: Sleep disturbance is recognized to be highly prevalent in people living with HIV (affecting ~29-97%). Women over the age of 40 years are particularly affected. It is not known however, if HIV infection independently contributes to sleep disturbance, or if the observed sleep disturbance is mostly due to psychosocial factors that can co-occur in people living with HIV. Therefore, we examined subjective and objective sleep parameters in women participating in the Women's Interagency HIV Study (WIHS) Chicago site. The WIHS study recruits women with and without HIV using similar methods, thereby minimizing psychosocial differences between them. Methods: Ninety women (46 HIV+ virally suppressed with antiretroviral therapy, 15 HIV+ viremic, and 29 HIV- women, average age 51 years) completed a sleep quality questionnaire (PSQI), a week of wrist actigraphy, and an overnight urine collection. Variables extracted from the wrist actigraphy included the weekly average total sleep time (TST) and sleep efficiency (SE). The overall night-time secretion of creatinine-adjusted levels of 6-sulphatoxymelatonin (melatonin metabolite, MLT) was extracted from the urine sample. Results: Many demographic and psychosocial factors known to influence sleep were not significantly different between the three groups (e.g. age, race/ethnicity, BMI, education, income, employment, stable housing, alcohol and substance use, depressive and PTSD symptoms; p>0.05). PSQI was elevated in all 3 groups but did not differ between groups (PSQI 6.4 HIV+ viremic, 6.7 HIV+ aviremic, 7.7 HIV-; p>0.05). Wrist actigraphy revealed similar sleep duration and sleep efficiency in all 3 groups with no group difference (TST: 6.7 h HIV+ viremic, 6.6 h HIV+ aviremic, 6.2 h HIV-; SE: 83.5% HIV+ viremic, 85.2% HIV+ aviremic, 84.7% HIV-, p>0.05). Melatonin metabolite concentration also did not differ between the groups (MLT: 21.6 HIV+ viremic, 25.0 HIV+ aviremic, 26.1 HIV-, p>0.05). Conclusion: While sleep disturbance is widely recognized in people living with HIV, HIV infection in and of itself does not appear to be systematically associated with greater sleep disturbance. Concomitant psychosocial factors likely play a greater role in contributing to sleep disturbance in HIV. Support (If Any): U01 AI034993